(3efXheI aj CdZGR fMhjI hTQMgGs
(3ChdgG (B:s
(3CWGdH Yde GdfMh CQTOJ aGSJeY eSGFd TJi JMJgf ahGFO s
(3BNQgG (B:s
(3aYd CeQ ef hdj jdj, hT GdKhH, ef hTj jTj gPG eG NWQ ddNGWQ GdcSjQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B230 - (3U(B231s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B316 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9304) s
Keywords: (3GdfMhs